2005
DOI: 10.1016/j.snb.2005.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A micromachined gas sensor based on a catalytic thick film/SnO2 thin film bilayer and thin film heater

Abstract: A micromachined gas sensor based on a catalytic thick film/SnO 2 thin film bilayer and a thin film heater was investigated for CH 4 sensing. The sensor demonstrated good sensitivity and high selectivity with low power consumption. The thin film heater and the SnO 2 thin film sensing layer were deposited on a Si micromachined structure having a silicon oxide-silicon nitride membrane. On the SnO 2 sensing layer, a Pd-Al 2 O 3 catalytic thick film was formed to oxidize interfering gases selectively. The sensor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 6 publications
(5 reference statements)
1
17
0
Order By: Relevance
“…At the same time, the sensor design guarantees more than 10 millions of heating cycles [33] that are enough for several years of operation.…”
Section: Quasi -Continuous Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the sensor design guarantees more than 10 millions of heating cycles [33] that are enough for several years of operation.…”
Section: Quasi -Continuous Measurement Methodsmentioning
confidence: 99%
“…The catalyst sensors have a dielectric support impregnated by Pt and Pd metals. The power consumption of these sensors during methane monitoring varies between 30 and 120 mW in continuous measurement mode [32] [33] . To the best of our knowledge the most energy efficient catalytic sensor is presented in Fig.…”
Section: Micromachined Silicon Based Catalytic and Semiconductor Sensmentioning
confidence: 99%
“…Pt-doped SnO 2 (Pt-SnO 2 ) thin film deposited on the SnO 2 sensor film shows a high methane sensitivity with a low power consumption and this opens a new way to realize battery-driven gas sensors. [30][31][32][33] Using the fluorescence XAFS to study the local structure of Pt in this fresh Pt-doped SnO 2 film at room temperature, we found that the Pt took a solid solution structure, being located at the Sn position of the SnO 2 lattice. 34 In literatures, a Pt metal cluster is considered to be an active structure in the reaction.…”
Section: B Xafs Measurementsmentioning
confidence: 99%
“…Therefore, a fast, accurate, and precise monitoring of trace greenhouse gas of CH 4 is essential. There are some methods for detecting methane, including chemical processes [3][4][5][6] and optical spectroscopy [7][8][9]. Optical spectroscopy for detecting gases is based on the Beer-Lambert law [10][11][12], in which the light attenuation is related to the effective length of the sample in an absorbing medium, and to the concentration of absorbing species, respectively.…”
Section: Introductionmentioning
confidence: 99%